The effect of self-confidence exercises to raise psychological resilience and perform some basic skills Tennis for youth (Damu Journal of Sport Sciences, 2024)
The importance of the research is evident in raising the psychological resilience of tennis players by using appropriate exercises, especially self-confidence exercises to raise the level of skill performance in a way that rises to obtain advanced results and the ability to perform correctly. The research problem was: Each game has its own psychological conditions in competing and achieving the required results and winning. Tennis is one of the sports that require psychological resilience to play long hours, and this can only be done by raising self-confidence, i.e. there must be psychological exercises that enhance self-confidence and through which psychological resilience is raised. The most important objectives of the research included: Identifying the effect of self-confidence exercises to raise psychological resilience and perform some basic skills in tennis for youth. Accordingly, the conclusions were: Self-confidence exercises enhance raising the level of psychological resilience and performing some basic skills in tennis for youth. While the researcher recommended: adopting self-confidence exercises because they enhance raising the level of psychological resilience and performing some basic tennis skills for young people.